Omnichannel B2B Marketing Activities for Industrial Enterprises: Integration, Challenges, and Performance Metrics : Penelitian - Mohammad Ruvi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study explores the potential of Omnichannel strategies in Business-to-Business (B2B) marketing, focusing on the effectiveness, challenges, and success factors of integrating online and offline activities in the industrial sector. The research originality lies in its comprehensive analysis of the barriers to seamless channel integration, filling gaps in the existing literature regarding cross-channel attribution and organizational silos in industrial firms. The study employs a mixed-methods approach, combining a systematic literature review, case studies of successful omnichannel implementations, and semi-structured interviews with industry experts. Empirical results reveal that integrated marketing activities are highly effective for lead nurturing and customer retention, with omnichannel strategies achieving higher engagement rates compared to single-channel approaches. However, challenges such as data fragmentation, organizational resistance, and technology implementation costs hinder widespread adoption. Key success factors include centralized data management, sales and marketing alignment, and consistent messaging across touchpoints. The findings have significant implications for B2B marketers, emphasizing the need for strategic infrastructure investment, continuous staff training, and policy frameworks that support digital transformation.